2014
DOI: 10.4103/0019-5413.139860
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Hip spica versus Rush pins for management of femoral diaphyseal fractures in children

Abstract: Background:Femoral fractures are common in children between 2 and 12 years of age and 75% of the lesions affect the femoral shaft. Traction followed by a plaster cast is universally accepted as conservative treatment. We compared primary hip spica with closed reduction and fixation with retrogradely passed crossed Rush pins for diaphyseal femur fracture in children. The hypothesis was that Rush pin might provide better treatment with good clinical results in comparison with primary hip spica.Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Ruhullah M et al 5 in their study showed that male: female ratio was 2.5:1. Mean age of injury was 4 years 4 months comparable with Ruhullah M et al, 5 where it was 6.4 years. Average duration of hospital stay was 1.5 days in our study.…”
Section: Discussionsupporting
confidence: 58%
“…Ruhullah M et al 5 in their study showed that male: female ratio was 2.5:1. Mean age of injury was 4 years 4 months comparable with Ruhullah M et al, 5 where it was 6.4 years. Average duration of hospital stay was 1.5 days in our study.…”
Section: Discussionsupporting
confidence: 58%
“…Breakage of spica cast before the intended period of application is a relatively common problem in the management of DDH [ 2 , 3 ]. Various modifications in plastering technique have been described to strengthen the spica cast.…”
Section: Introductionmentioning
confidence: 99%
“…The article titled, “Hip spica versus Rush pins for management of femoral diaphyseal fractures in children” published in Indian Journal of Orthopaedics 1 , issue 5, Vol. 48, pages 488-94, is being retracted.…”
mentioning
confidence: 99%